UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN MELALUI BIMBINGAN BERKELANJUTAN DI SMPK MARIA IMAKULATA MAGEPANDA - Orcelina da Toa, Valentina (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The purpose of this study is to improve teacher competency in preparing lesson plans through ongoing guidance at SMP Imakulata Maria Magepanda. This research is in the form of School Action Research. The method used in this research is descriptive method, using percentage techniques to see the increase that occurs from cycle to cycle. Analysis of the data used in this study is the analysis of qualitative data sourced from primary and empirical data. The results of this study indicate that there is an increase between cycles, where the percentage ratio of the components of school identity is 19%, the comparison of the percentage components of the subject's identity is 20%, the percentage of class / semester components both cycle I and cycle II is 100%, the percentage ratio of the principal material components is 2%, the comparison of the percentage of time allocation components is 2%, the comparison of the percentage of learning objectives components is 14%, the percentage ratio of basic competency components and indicators of competency achievement is 14%, the percentage ratio of learning material components is 2%, the percentage ratio of learning method components is 6%, comparison of the percentage of learning media components is 10%, comparison of the percentage of learning resource components is 6%, comparison of the percentage of components of learning activities steps is 13%, comparison of the percentage of assessment components of learning outcomes is 13%. In cycle I the average value of the RPP component was 87%, in cycle II the average value of the RPP component was 96%, an increase of 9%. This shows that the implementation of ongoing guidance can improve teacher competency in preparing lesson plans.